Development of black ink for calligraphy purpose in the production of Al-Quran manuscript - Abdul Rahim, Fatin Fatiha; Jai, Junaidah; Hamzah, Fazlena; Abu Bakar, Noor Fitrah (2017)
Commercialised calligraphy inks are currently formulated for general purposes and is not to be practiced solely for the writings of Al-Quran. Thus the usage on Al-Quran is uncertain due to the unknown ingredients used. The virtue of this work is to develop halal and genuine formulations of black inks for calligraphy purpose in the production of Al-Quran manuscript. The black ink produced is required to have few properties; rich solid black, soft handling, fast drying time, non-lifting, non-feathering and waterproof. Pigment used include graphene, charcoal and lampblack. The binders are shellac and acrylic emulsion while solvent used are glycerol and ethanol. From the chosen pigments, binders and solvent, 19 formulation of inks were developed by manipulating the type and amount of each element. Evaluation of all 19 inks produced were done by an expert calligrapher using a professional scale. From the evaluation, one ink was chosen to have the best characteristics of an ink (ink code S9) with formulation of 0.3 g lampblack and 13 mL shellac. The produced black ink has fulfilled the requirement by the calligraphy expert.